POWER Learning : Strategies for Success in College and Life - Feldman, Robert S. (New York McGraw-Hill, 2005)
Offering a system for critical thinking and problem solving, this work aims to maximize students' potential for success in college and in life. Using the class-tested principles of the P O W E R (Prepare, Organize, Work, Evaluate, and Rethink) system, it enables students gain a sense of mastery and achievement as they move through the text.
Includes Color Illustrations and Index.
Keywords: Study Skills -- Success -- Life skills